MBSE-Lite: a framework for adopting model-based systems engineering in small and medium-sized enterprises in South Africa - Nanfuka, Justine Geraldine; Oosthuizen, Rudolph (Business, Management and Economics Engineering, 2023)
Purpose – This research aims to characterise the landscape and factors for successfully implementing Systems Engineering (SE) and Model-Based Systems Engineering (MBSE) in the enterprise.Research methodology – The study investigated the factors across different industries that affect the success of MBSE in an enterprise using a survey questionnaire. The research focussed on the uptake and implementation of MBSE in Small and Medium-sized enterprises (SMEs) in South Africa. More than 100 industry professionals participated in the study.Findings – The survey revealed that SMEs have trouble adopting and implementing MBSE because they are unaware of its applicability and lack economic justification and support from upper management. Quantitative data analysis assessed how factors such as MBSE training, existing SE processes in the enterprise, and how long the company has been using MBSE contribute to the success of MBSE adoption in SMEs.Research limitations – The population size limited the study reached and the time available to conduct the research. However, it does not reduce the results’ strength and validity.Practical implications – The analysis showed that training and an existing SE structure are highly significant, while the age of MBSE in the enterprise does not correlate with its success. Therefore, these results proposed an adoption framework for SMEs in South Africa to aid MBSE adoption by incorporating training and a clear uptake and implementation process.Originality/Value – This research builds on the growing body of literature about implementing MBSE and enterprises. The conclusions provide valuable insights and guidelines for implementing MBSE in SMEs.